The effects of air lead pollution from automobile emission on the health of traffic policemen in Metro Manila - Luu Ngoc Hoat.
The study concerned about the possible effects of air lead pollution from automobile exhaust on the health of traffic policement working in Metro Manila. The major outcome of interest was erthrocyte protoporphyrin levels that can express inpairments of the heme synthesis system due to lead. Besides that, hemoglobin was also used for determining further lead influences on the hematological system. In order to evaluate the possible effects of long term lead exposures from vehicular emission of the traffic policement on the cardiovascular and autonomous neuro-system, cardiac output and peripheral resistance were used. Because of time and budget problems, only duration of employment was considered as exposure factor of working exposure situation of the study subjects. Other several risk factors were selected as potential confounding factors. The results showed that EP levels of forty study subjects are not high with a mean and standard deviation is 47.4 +- 15.4 ug/ 100 mlE. Only eight among forty subjects had EP levels more than upper normal limit (62 ug/ 100mlE). Nobody ha EP levels at the limit of lead poisoning (250 ug/ 100 mlE). For hemoglobin levels, the average value of thirty three subjects is 13.7 +- 1.0 g/100 ml; nine of them (27 ) had this value less than lower normal limit (13 g/100 ml). The average cardiac output and peripheral resistance of the study subjects are 3.4 +- 0.7 l/minute and 2529 +- 846 din/sec/cm (-5), respectively. If the cut-off point which was previously used in Vietnam is applied to the present study, 42.5 of the subjects had cardiac output lower than normal value and 47.5 had peripheral resistance higher than upper normal limit. In this study, only duration of employment was exposure factor. However, no statistically significant relationship was found between this variable and four outcomes when correlation coefficients were used. When controlling for potential confounders on these relationships through the use of multiple regression analysis, the relationship between duration of employment and hemoglobin was significant at p-value equal to 0.05. From the ry of each of the four multiple regression equations which examined the relationship between the biologial indicators, duration of employment and the six potential confounders, it was noted that only 19 of the variablity of EP levels could be explained due by the variations of these seven independent variables (ry = 0.19). For the other outcomens, the seven independent variables could explain only 26 ; 12 and 17 of the variability of hemoglobin, cardiac output and peripheral resistance, respectively.
Thesis (Master of Science in Epidemiology)--University of the Philippines Manila.
Keywords: Air -- Pollution